Investigation of the relationship between weight self-stigma, emotional eating, and diet satisfaction in obese individuals - Dilsiz, Naci Berat; Arslan, Sedat (The European Research Journal, 2023)
Objectives: Obese people are often stigmatized and discriminated against as unmotivated, incompatible, sloppy, undisciplined, and lazy because of their excess weight. The stigma associated with weight has serious adverse effects on mental health, social functioning, and physical health. It has been suggested that weight stigma can be internalized and lead to the development and maintenance of self-stigma. Methods: Personal Information Form, Turkish Emotional Eating Scale (EES), Weight Self-Stigma Scale (WSSQ), and Diet Satisfaction Scale (DSS) were used. Results: One hundred forty-five volunteer obese individuals who applied to the Diet Clinic and whose informed consent was obtained were included in the study. When the differences between the scale scores of the individuals according to demographic, health, and nutrition findings are examined, it is seen that the TEES scores according to the gender and income status of the obese individuals, the WSSQ scores according to the gender and employment status of the obese individuals, and the DSS scores according to the income status of the obese individuals, the psychological diagnosis status made by the physician, It was found that there was a significant difference according to the chronic disease states and the number of daily snacks (p < 0.05 and p < 0.001, respectively). Conclusions: When the relationship between the scales was examined, a significant correlation was found between the WSSQ scores of obese individuals and their EES scores. It was found that there was a statistically significant effect of WSSQ scores on EES scores. It is thought that the findings of this study will contribute significantly to the relevant literature.